2022
DOI: 10.2478/johh-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

3D numerical modeling of flow characteristics in an open channel having in-line circular vegetation patches with varying density under submerged and emergent flow conditions

Abstract: In the marine ecological system, the prime role of water management and durability of an ecosystem is being played by the vegetation patches. The vegetation patches in open channels can significantly affect the flow velocity, discharge capacity and hinder energy fluxes, which ultimately helps in controlling catastrophic floods. In this study, the numerical simulation for turbulent flow properties, i.e. velocity distribution, Reynolds stresses and Turbulent Intensities (TI) near the circular vegetation patches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Based on the velocity profiles observed, it's evident that an upward trend exists: as depth increases from the surface, velocity also increases. This finding aligns with the conclusions drawn by [16] as seen on figure (7), [28], who examined fluid flow in an open trapezoidal channel and similarly found that flow velocity correlates positively with depth.…”
Section: Fig 7 Validation Of Resultssupporting
confidence: 92%
“…Based on the velocity profiles observed, it's evident that an upward trend exists: as depth increases from the surface, velocity also increases. This finding aligns with the conclusions drawn by [16] as seen on figure (7), [28], who examined fluid flow in an open trapezoidal channel and similarly found that flow velocity correlates positively with depth.…”
Section: Fig 7 Validation Of Resultssupporting
confidence: 92%
“…Recent numerical studies of submerged canopies include the analysis of rigid fixed submerged fibers, 75,76 2D models of fluid flow interacting with submerged rod-like structures, as in References 10,11,77, as well as immersed 2D flaps interacting with the 3D flow around it, compare of References 8,9. Due to the large number of fibers required to model such canopies realistically, the resolution of such setups in 3D poses a challenge regarding the model complexity.…”
Section: Submerged Vegetationmentioning
confidence: 99%
“…In References 70,71, these phenomena have been studied experimentally and, in References 72–74, efforts have been made to quantify their effect on the flow around them by analytical solutions to roughness and density variation models. Recent numerical studies of submerged canopies include the analysis of rigid fixed submerged fibers, 75,76 2D models of fluid flow interacting with submerged rod‐like structures, as in References 10,11,77, as well as immersed 2D flaps interacting with the 3D flow around it, compare of References 8,9. Due to the large number of fibers required to model such canopies realistically, the resolution of such setups in 3D poses a challenge regarding the model complexity.…”
Section: Numerical Examplesmentioning
confidence: 99%